Faktor pendorong dan penghambat adopsi pupuk organik cair pada usahatani padi di Kabupaten Tana Toraja - Herlina Salinding; Awaluddin Yunus; Musdalifah Mahmud (LP3M Universitas Putra Bangsa, 2026)
Dependence on chemical fertilizers has resulted in declining land quality, groundwater pollution, and even higher agricultural production costs due to fluctuating chemical fertilizer prices. Furthermore, frequent fertilizer crises in recent years have demonstrated the fragility of dependence on inorganic fertilizers in the national agricultural system. Therefore, a transformation towards environmentally friendly, sustainable agriculture is urgently needed. The data analysis technique used in this study was a scoring technique, where the researcher's field observations were analyzed and narrated according to a written methodology. The scoring process for respondents' answers was carried out by creating classifications and categories that matched the respondents' assumptions or opinions. A Likert scale was used to determine the score for each respondent's answer choices. The Likert scale is used to measure the attitudes, opinions, and perceptions of an individual or group of people regarding social phenomena. The results showed that the driving factors, such as affordable fertilizer prices, support from extension workers, and social support from the community, scored above 82%. This indicates that external conditions are quite supportive of the use of fertilizers. The main obstacles still faced are the limited availability of fertilizers in the field and farmers' long-standing habit of relying on chemical fertilizers. Furthermore, it is necessary to increase the availability of POC in the market through collaboration with producers and farmer groups, provide continuous technical assistance, including demonstration plots that show real results of increased rice production with POC and strengthen subsidy policies or special incentives for farmers who switch from chemical fertilizers to organic fertilizers as well as farmer groups and agricultural extension workers need to continue to be supported to remain the driving force for the spread of environmentally friendly innovations such as POC.